2016
DOI: 10.7567/jjap.55.07mc06
|View full text |Cite
|
Sign up to set email alerts
|

B2O3: Grain boundary material for high-Ku CoPt–oxide granular media with low degree of intergranular exchange coupling

Abstract: The magnetic properties and structures of Co80Pt20–30 vol % oxide (ZrO2, Cr2O3, Y2O3, Al2O3, MnO, TiO2, WO2, SiO2, Mn3O4, WO3, Co3O4, MoO3, and B2O3) granular media deposited at room temperature were investigated. As a result, the following were found. 1) By employing oxides with low melting point temperatures as the granular media, magnetic grains with high saturation magnetization ( ) and perpendicular magnetic anisotropy ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…To realize these requirements, the segregation of oxides material into the grains boundaries and the promotion of phase separation between the oxide and metal material are essential. Generally, for the grain boundary materials, oxides material which do not dissolve into the CoPt metal, such as SiO 2 , 3 8,9 Furthermore, by mixing low T m B 2 O 3 with high T m oxides, media with small magnetic grain size can be obtained. 10 It is also shown that the introduction of a buffer layer (BL) underneath the granular media has a great impact on promoting the intergranular exchange decoupling of the media.…”
Section: Introductionmentioning
confidence: 99%
“…To realize these requirements, the segregation of oxides material into the grains boundaries and the promotion of phase separation between the oxide and metal material are essential. Generally, for the grain boundary materials, oxides material which do not dissolve into the CoPt metal, such as SiO 2 , 3 8,9 Furthermore, by mixing low T m B 2 O 3 with high T m oxides, media with small magnetic grain size can be obtained. 10 It is also shown that the introduction of a buffer layer (BL) underneath the granular media has a great impact on promoting the intergranular exchange decoupling of the media.…”
Section: Introductionmentioning
confidence: 99%
“…One reason for the exsolution of Co and formation of Co 3 O 4 is that the Co cations near the surface of PBCC grains are strongly attracted by the surface oxygen vacancies, whose concentration increases under polarization conditions. , In addition, the limited initial physical contact between the electrode and electrolyte can result in local heating due to the release of Joule heat as oxygen ions transport at the electrode–electrolyte interfaces during polarization, which further increases the concentration of surface oxygen vacancies (Figure a). The in situ -formed Co 3 O 4 phase with a relatively low melting temperature , probably serves as a bridging layer to firmly adhere the PBCC-d750 electrode to the GDC barrier layer (Figure b). The promotional effect of this bridging layer is similar to the enhancement of interfacial contact by diffusion of in situ generated molten carbonate from the cathode to the electrolyte in the case of carbonate-superstructured SOCs …”
Section: Resultsmentioning
confidence: 99%
“…Previously, we found that a medium with magnetic grains of high magnetocrystalline anisotropy (K u ) was successfully realized when a lowmelting-point oxide, B 2 O 3 , was used as the grain boundary material. 9) However, the grain diameter of the CoPt-B 2 O 3 granular medium is larger than those of granular media with multiple oxides. 10) One of the methods of reducing the grain diameter of the granular medium is to insert a nucleation layer with small grain diameter.…”
Section: Introductionmentioning
confidence: 99%